Twelve-month utilization rates and adequacy of treatment for mental health and substance use disorders in Argentina - Cia, Alfredo H. (2019)
OBJECTIVE: To estimate the 12-month prevalence of mental health services utilization (overall and by type of service sector), the adequacy of treatment provided, and sociodemographic correlates in the Argentinean Study of Mental Health Epidemiology (ASMHE). METHODS: The ASMHE is a multistage probability household sample representative of adults in urban areas of Argentina. The World Health Organization World Mental Health Composite International Diagnostic Interview (WMH-CIDI) was used to evaluate psychiatric diagnosis and service utilization. RESULTS: Among those with a disorder, 27.6% received any treatment in the prior 12 months. Of these, 78.3% received minimally adequate treatment using a broad definition and only 43.6% using a stringent definition. For individuals with a disorder, more services were provided by mental health professionals (17.7%) than by general medical professionals (11.5%) or non-healthcare sectors (2.6%). Younger individuals with low education and income were less likely to receive treatment; those never married and those with an anxiety or mood disorder were more likely to receive treatment. Among those in treatment, treatment was least adequate among younger individuals with low education and low income. CONCLUSIONS: Policies to increase access to services for mental health disorders in Argentina are needed, as is training for primary care practitioners in the early detection and treatment of psychiatric disorders.